Lekarze i firmy farmaceutyczne – standardy etyczne wzajemnych relacji w Unii Europejskiej - Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2012)
Within last twenty years in the European Union much regulation concerning advertisements of drugs changed. The aggressive marketing operations of producers of medicines caused that new solutions, not only legal but also ethical, had appeared. The European Union is imposing reliable solutions upon its members in the form of directives to which they must adapt their law. They can however decide to choose stricter law than the one which is recommended to them. The European Federation of Pharmaceutical Industry and Associations – voluntary organization consisting associations of pharmaceutical companies from lots of countries is acting on similar principles. Each of the members belonging to it can implement its own, more restrictive regulation in the national ethical code than a Federation is ordering. Main purpose of this article is reading what legal and ethical solutions of pharmaceutical marketing were accepted in selected countries of the European Union. Whether they are stricter than the ones imposed upon them by European Union? How in this background Polish regulations are looking like? In the article also examples of the law-breaking and ethical principles by producers of medicines in the European Union will be presented. It will show sanctions taken out towards them for this reason. A question will be put: are various penalties able effectively to scare the pharmaceutical industry off the unethical or even unlawful advertising?